2015
DOI: 10.1186/s12929-015-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic effect of a novel temozolomide analog on nasopharyngeal carcinoma in vitro and in vivo

Abstract: BackgroundMany patients with nasopharyngeal carcinoma (NPC) face poor prognosis. Due to its hidden anatomical location, the tumor is usually diagnosed quite late, and despite initially successful treatment with radiation and cisplatin, many patients will relapse and succumb to the disease. New treatment options are urgently needed. We have performed preclinical studies to evaluate the potential NPC therapeutic activity of a newly developed analog of temozolomide (TMZ), an alkylating agent that is the current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…“Tumor + cisplatin” group, mice injected with EAC cells with subsequent infusion of 0.05 ml of cisplatin (0.5 mg/ml), an antitumor drug [ 29 , 30 ], on days 3, 7 and 11 experimental days. Cisplatin has been often used as a reference drug [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…“Tumor + cisplatin” group, mice injected with EAC cells with subsequent infusion of 0.05 ml of cisplatin (0.5 mg/ml), an antitumor drug [ 29 , 30 ], on days 3, 7 and 11 experimental days. Cisplatin has been often used as a reference drug [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Temozolomide (TMZ) is a novel type of glioma therapeutic drug, which is able to penetrate the blood-brain barrier to exert targeted therapeutic effects on brain tumor tissue ( 5 , 6 ). To date, studies have aimed to enhance the efficacy and reduce the toxic side effects of TMZ by reconstructing its chemical structure ( 7 , 8 ). To build on these previous studies, the present study utilized the molecular biological differences between tumor and normal cells to design TMZ derivatives with enhanced selectivity and targeting activities through rational computer-aided drug design (CADD).…”
Section: Introductionmentioning
confidence: 99%
“…These cytotoxic effects of TMZ decay rapidly within the first few hours of treatment. Previous studies from this laboratory showed that when we incubate TMZ in medium at 37 °C, it loses its cytotoxicity after 2 h, while NEO212 loses its cytotoxicity after 24 h of incubation at 37 °C in the medium[16, 27, 28]. To determine whether there is a relationship between the cytotoxic effects of NEO212 and its ability to block the migration of GSCs, we treated USC02 cells with NEO212 for 24 h; then the supernatant was replaced with fresh medium without the drug in half of the cell cultures, or medium with NEO212 was not removed in the other half; and the cells were incubated for an additional 48 h-period.…”
Section: Resultsmentioning
confidence: 99%